Croton urucurana Baill. Ameliorates Metabolic Associated Fatty Liver Disease in Rats - Auth, Pablo Alvarez; da Silva, Gustavo Ratti; Amaral, Eduarda Carolina; Bortoli, Victor Fajardo; Manzano, Mariana Inocencio; de Souza, Lauro Mera; Lovato, Evellyn Claudia Wietzikoski; Ribeiro-Paes, João Tadeu; Gasparotto Junior, Arquimedes; Lívero, Francislaine Aparecida dos Reis (Frontiers in Pharmacology, 2022)
Background: Metabolic associated fatty liver disease (MAFLD) affects a quarter of the worldwide population, but no drug therapies have yet been developed. Croton urucurana Baill. (Euphorbiaceae) is a medicinal species, that is, widely distributed in Brazil. It is used in popular medicine to treat gastrointestinal, cardiovascular, and endocrine system diseases. However, its hepatoprotective and lipid-lowering effects have not yet been scientifically investigated. Aim of the study: The present study investigated the effects of an extract of C. urucurana in a rat model of MAFLD that was associated with multiple risk factors, including hypertension, smoking, and dyslipidemia. Material and Methods: The phytochemical composition of C. urucurana was evaluated by liquid chromatography-mass spectrometry. Spontaneously hypertensive rats received a 0.5% cholesterol-enriched diet and were exposed to cigarette smoke (9 cigarettes/day for 10 weeks). During the last 5 weeks, the animals were orally treated with vehicle (negative control [C-] group), C. urucurana extract (30, 100, and 300 mg/kg), or simvastatin + enalapril (two standard reference drugs that are commonly used to treat dyslipidemia and hypertension, respectively). One group of rats that were not exposed to these risk factors was also evaluated (basal group). Blood was collected for the analysis of cholesterol, triglyceride, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels. The liver and feces were collected for lipid quantification. The liver was also processed for antioxidant and histopathological analysis. Results: The main constituents of the C. urucurana extract were flavonoids, glycosides, and alkaloids. The model successfully induced MAFLD, reflected by increases in AST and ALT levels, and induced oxidative stress in the C- group. Treatment with the C. urucurana extract (300 mg/kg) and simvastatin + enalapril decreased plasma and hepatic lipid levels. In contrast to simvastatin + enalapril treatment, C. urucurana reduced AST and ALT levels. Massive lesions were observed in the liver in the C- group, which were reversed by treatment with the C. urucurana extract (300 mg/kg). Conclusion:C. urucurana extract exerted promising hepatoprotective and lipid-lowering effects in a preclinical rat model of MAFLD.